Chemotaxis of Vδ2 T cells to the joints contributes to the pathogenesis of rheumatoid arthritis. Issue 12 (2nd September 2017) - Mo, Wen-Xiu; Yin, Shan-Shan; Chen, Hua; Zhou, Chen; Zhou, Jia-Xin; Zhao, Li-Dan; Fei, Yun-Yun; Yang, Hua-Xia; Guo, Jing-Bo; Mao, Yu-Jia; Huang, Lin-Fang; Zheng, Wen-Jie; et al.
Abstract : Objectives: To explore the role of Vδ2 T cells in the pathogenesis of rheumatoid arthritis (RA). Methods: Sixty-eight patients with RA, 21 patients with osteoarthritis and 21 healthy controls were enrolled in the study. All patients with RA fulfilled the 2010 American College of Rheumatology/European League Against Rheumatism criteria for RA. Peripheral Vδ2T population, chemokine receptor expression and proinflammatory cytokine secretion were quantified by flow cytometry. The infiltration of Vδ2 T cells within the synovium was examined by immunohistochemistry and flow cytometry. The effect of tumour necrosis factor (TNF)-α and interleukin (IL)-6 on Vδ2 T migration was determined by flow cytometry and transwell migration assay. Results: Peripheral Vδ2T cells, but not Vδ1 T cells, were significantly lower in patients with RA, which was negatively correlated with disease activity gauged by Disease Activity Score in 28 joints. Vδ2 T cells from RA accumulated in the synovium and produced high levels of proinflammatory cytokines including interferon-γ and IL-17. Phenotypically, Vδ2 T cells from RA showed elevated chemotaxis potential and expressed high levels of chemokine receptors CCR5 and CXCR3, which was driven by increased serum TNF-α through nuclear factor kappa B signalling. In vivo, TNF-α neutralising therapy dramatically downregulated CCR5 and CXCR3 on Vδ2 T cells and repopulated the peripheral Vδ2 T cells in patients with RA. Conclusions: High levels of TNF-α promoted CCR5 and CXCR3 expression in Vδ2 T cells from RA, which potentially infiltrated into the synovium and played crucial roles in the pathogenesis of RA. Targeting Vδ2 T cells might be a potential approach for RA.